Cerebellar Syndrome as a Presentation of Pulmonary Hypertension - Pablo Ruiz-Sada; María-Jesús Iguzquiza-Pellejero; María-José Esquillor-Rodrigo; Lara Palacios-García (Internal Medicine, 2016)
Coincident focal signs and dyspnea can lead to diverse conclusions. However, if they present in the context of a genetic cardiac abnormality a straight forward link can be established. Patent foramen ovale (PFO) can cause a wide range of manifestations. Not always suspected in the Accident and Emergency (A&E) unit, PFO is the most common cardiac abnormality and should be ruled out when systemic embolisms happen in the absence of cardiac arrhythmia or advanced arteriosclerosis. We present a complex case of a lady in which both PFO and an advanced rheumatic condition were the underlying causes of pulmonary hypertension (PH).